The spatial analysis of the population settlement peculiarities of Volyn region using centrographic method - Лажнік, Володимир; Пугач, Сергій (Human Geography Journal, 2017)
To analyze the characteristics of population settlement of certain areas different methodological approaches and techniques are used, among which сentrographic method occupies a special place. Centrographic method allows to determine the center of population gravity, the degree of its concentration around the central points of the territory, to identify the space-time changes in their placement, to compare the centers of population areas (democenters) with the gravity centers of the other geographical phenomena, which are obtained by similar formulas.By сentrographic methods using the geographic coordinates and location of the geographical center of Volyn region and the center of gravity of all urban and rural population of the region according to Census of 1979, 1989, 2001 are specified. The dynamics and trajectory of weight shift in population over the investigated period are analyzed, the values of discentrіsitets in the distribution of centers of gravity of all are determined, the urban and the rural population regarding the geographical center of the region. The basic causes of demographic displacement centers are established. On the basis of calculation of standard deviation centers the degree of concentration of all urban and rural population around their centers is revealed, and also the decrease of regional system of population settlement. The causes of spatial asymmetry in the distribution of population in the region are set, including important activation of suburbanizational processes inLutsktown agglomeration and around urban settlements of the area. The parameters of standard deviation and scattering ellipse are calculated taking into account the ellipticity of the region territory, show that urban population of the region has a higher degree of concentration around its center of gravity than the rural population, because of the small number of urban areas on the periphery of the region and in its border areas.